Multi-scale optical coherence tomography imaging and visualization of Vermeer's Girl with a pearl earring - Callewaert, Tom; Guo, Jerry; Harteveld, Guusje; Vandivere, Abbie; Eisemann, Elmar; Dik, Joris; Kalkman, Jeroen (Optics express, 2020)
We demonstrate multi-scale multi-parameter optical coherence tomography (OCT) imaging and visualization of Johannes Vermeer’s painting Girl with a Pearl Earring . Through automated acquisition, OCT image segmentation, and 3D volume stitching we realize OCT imaging at the scale of an entire painting. This makes it possible to image, with micrometer axial and lateral resolution, an entire painting over more than 5 orders of length scale. From the multi-scale OCT data we quantify multiple parameters in a fully automated way: the surface height, the scattering strength, and the combined glaze and varnish layer thickness. The multi-parameter OCT data of Girl with a Pearl Earring shows various features: Vermeer’s brushstrokes, surface craquelure, paint losses, and restorations. Through an interactive visualization of the Girl , based on the OCT data and the optical properties of historical reconstructions of Vermeer’s paint, we can virtually study the effect of the lighting condition, viewing angle, zoom level and presence/absence of glaze layer. The interactive visualization shows various new painting features. It demonstrates that the glaze layer structure and its optical properties were essential to Vermeer to create an extremely strong light to dark contrast between the figure and the background that gives the painting such an iconic aesthetic appeal.